Integration of a solar thermal system in a medium-sized brewery using pinch analysis: Methodology and case study. (25th February 2017) - Eiholzer, Tobias; Olsen, Donald; Hoffmann, Sebastian; Sturm, Barbara; Wellig, Beat
Highlights: Methodologies to reduce energy consumption in batch processes are presented. Pinch analysis is used to improve energy efficiency. Integration potential for solar heat is presented on a Scottish brewery case study. Governmental support is important in a company's investment in renewables. Abstract: In the food industry a major portion of thermal energy is required for low temperature applications (below 100 °C). As a consequence, there is a significant potential to substitute fossil fuels by the use of solar heat. This paper presents a methodology that first uses pinch analysis to optimize a medium-sized Scottish brewery from a direct heat recovery perspective followed by the integration of a solar thermal system. Both the time average model and time slice model were used to determine direct and indirect heat recovery potentials. In a second stage, an optimization of a chosen integration point was conducted to assess the viability of the resulting design concept. The economic analysis includes an assessment of the impact of restrictions in the UK government's Renewable Heat Incentive program. It was determined that since solar thermal systems are financially supported up to an installed capacity of 200 kW, solar heat can only account for a maximum of 7.7% of the heat demand based on the investigated brewery. However, if there was no limitation in capacity, from an economic point of view, the solar fraction could almost be doubled drawing into question the need for the restriction. Nevertheless, a CO2 saving potential of approximately 38 tons per year in conjunction with a payback period of 6.4 years was determined.